Collaboration in Education: The Phenomenon and Process of Working Together - Goulet, Linda; Krentz, Caroline; Christiansen, Helen (Alberta Journal of Educational Research, 2003)
In this article we propose a model for collaboration in education. We begin by examining theroots of collaboration in consultation, collegiality, and cooperation. We then delineate thefeatures of collaboration as phenomenon and process, offering the view that through talk,action, and reflection among individuals a community of learners emerges. Finally, wesuggest that collaboration can create a space that enables us to challenge taken-for-grantedways of working together and to bring about transformation in educational practice.